72.3k views
0 votes
A pile of bricks of mass M is being raised to the tenth floor of a building of height H = 4y above the ground by a crane that is on top of the building. During the first part of the lift, the crane lifts the bricks a vertical distance h1=3y in a time t1=4T. During the second part of the lift, the crane lifts the bricks a vertical distance h2=y in t2=T. Which of the following correctly relates the power P1 generated by the crane during the first part of the lift to the power P2 generated by the crane during the second part of the lift?

A. P2=4P1
B. P2=43P1
C. P2=P1
D. P2=34P1
E. P2=13P1

User HydTechie
by
5.1k points

1 Answer

7 votes

Complete Question

A pile of bricks of mass M is being raised to the tenth floor of a building of height H = 4y above the ground by a crane that is on top of the building. During the first part of the lift, the crane lifts the bricks a vertical distance h1=3y in a time t1=4T. During the second part of the lift, the crane lifts the bricks a vertical distance h2=y in t2=T. Which of the following correctly relates the power P1 generated by the crane during the first part of the lift to the power P2 generated by the crane during the second part of the lift?


A.\ \ P_2=4P_1


B.\ \  P_2=(4)/(3) P1


C.\ \  P_2=P_1


D. \ \ P_2=(3)/(4) P_1


E. \ \ \ P_2=(1)/(3) P_1

Answer:

The correct option is B

Step-by-step explanation:

From the question we are told that

The mass of the brick is M

The height height of the 10th floor is H = 4y

The height attained during the first part of the lift is
h_1 =  3y

The time taken is
t_1 =  4T

The height attained during the second part of the lift is
h_2  = y

The time taken is
t_2  =  T

Generally the velocity of the crane during the first lift is mathematically represented as


v_1  =  (h_1)/(t_1)

=>
v_1  =  (3y)/(4T)

Generally the velocity of the crane during the first lift is mathematically represented as


v_1  =  (h_2)/(t_2)

=>
v_1  =  (y)/(T)

Generally the power generated during the first lift is


P_1 =  F_1 *  v_1

Here
F_1 force applied during the first lift which is mathematically represented as


F_1  =  M  *  g here g is the acceleration due to gravity

So


P_1 =  Mg * (3y)/(4T)

Generally the power generated during the second lift is


P_2 =  F_2 *  v_2

Here
F_2 force applied during the second lift which is mathematically represented as


F_2  =  M  *  g here g is the acceleration due to gravity

So


P_2 =  Mg * (y)/(T)

So the ratio of the first power to the second power is


(P_1)/(P_2)  =  (Mg * (3y)/(4T)[)/(Mg * (y)/(T))

=>
(P_1)/(P_2)  = (3)/(4)

=>
P_2 = (4)/(3) P_1

User Josshad
by
5.1k points